Sanggah Kemulan Nganten dan Pelangkiran: obyek penentu keberlangsungan rumah tinggal tradisional Desa Pedawa, Bali - Prajnawrdhi, Tri Anggraini; Pebriyanti, Ni Luh Putu (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2016)
Balinese traditional architecture’s form and character are associated to its culture, custom and religious system of the Balinese. Traditional Balinese house as part of the Nusantara Architecture are inherited from our ancestors and have become the evident of our history. Tri Hita Kharana is the concept which reflect a close relationship between the Balinese with the nature and the God, which become the foundation of traditional setllement in Bali Aga vilages, thus it also become the main concept in preserving Balinese traditional architecture. The unique character of traditional house in desa Pedawa formed by people’s belief of their ancestor; their tradition as palm sugar maker; their nature and surrounding areas; and their way of life. This research aimed to discover the important factor from this traditional house which preserve this house to this moment. Case study method includes field observation, interview and historical study with the use of descriptive analysis has presented that Sanggah Kemulan Nganten and Pelangkiran are the two most important factors in preserving the traditional house in Desa Pedawa.Keywords: traditional house, Pelangkiran, Sanggah Kemulan Nganten